The Aneurysmal Dilatation of Bovine Jugular Venous Conduit After Pulmonary Artery Reconstruction - Omay, Oguz; Can Vuran, Ali; Gumus, Burcak; Ezgi, Tuncay; Yoruker, Uygar; Turkoz, Riza (Annals of Medical Research, 2021)
None